SIFAT FISIK DAN KIMIA PELEPAH AREN (Arenga pinnata Merr) UNTUK BAHAN BAKU ALTERNATIF PULP DAN KERTAS - Dewi Aminah; Fatriani Fatriani; Henny Arryati (Jurnal Sylva Scienteae, 2020)
The purpose of this study was to analyze the chemical components and dimensions of palm frond fibers. The method used is the TAPPI Standard and Haque et al. 2015 for testing chemical components, Schultze's method for fiber dimensions. The results of this study, the palm fronds chemical component, which is moisture content ranging from 17-19%, is included in the high category because it is above 10%, extractive content ranges from 19-59% including high category because it exceeds 10%, lignin content ranges from 21-25% including medium category Cellulose content ranged from 21-27% including the low cellulose category because <40%, holocellulose content ranged from 48-49% including the medium category and hemicellulose content ranged from 22-23% including the low category. Fiber dimensions include fiber length, fiber diameter, lumen diameter and fiber wall thickness and fiber derivative values including Runkell Ratio, Felting Power, Muhleph Ratio, Coofficient Of Rigidity And Felexibility Ratio including quality class II.